Performance of High School Students in Vhembe District - Kyei, Kwabena A; Maboko, T (Journal of Economics and Behavioral Studies, 2016)
Despite the attempts by South African government to make education accessible to all by introducing free food and free textbooks at the primary school level, there is still high failure rate in mathematics and science in high schools in the country. This study makes attempt to establish some factors that affect the performance of students, especially in science subjects in high schools in the Vhembe district in the Limpopo province. A survey was conducted in 17 high schools randomly sampled in the Vhembe district. Purposive sampling was used to get the grade 11 and 12 students and their teachers. About 700 students, 70 teachers and 17 principals were interviewed. The study concludes that the overall pass rate is 70% but the rate in mathematics and science is hardly 40%; and the key factors affecting performance are lack of laboratory for practical, awards, shuffling and textbooks. The study recommends that science laboratories be built in schools, textbooks be supplied in good time and teachers to motivate students by giving awards.